a) $0.9 \cdot (-0.4) - 0.7 \cdot (-0.4) = -0.36 + 0.28 = -0.08$
б) $-\frac{4}{13} \cdot 0.6 - 0.6 \cdot (-\frac{9}{13}) = -\frac{4}{13} \cdot \frac{6}{10} + \frac{6}{10} \cdot \frac{9}{13} = \frac{6}{10} \cdot (-\frac{4}{13} + \frac{9}{13}) = \frac{3}{5} \cdot \frac{5}{13} = \frac{3}{13}$
в) $-\frac{8}{11} \cdot \frac{5}{6} + \frac{5}{6} \cdot \frac{3}{11} = \frac{5}{6} \cdot (-\frac{8}{11} + \frac{3}{11}) = \frac{5}{6} \cdot (-\frac{5}{11}) = -\frac{25}{66}$
г) $1\frac{2}{3} \cdot 2.8 - 2\frac{2}{9} \cdot (-6.2) = \frac{5}{3} \cdot \frac{28}{10} + \frac{20}{9} \cdot \frac{62}{10} = \frac{5}{3} \cdot \frac{14}{5} + \frac{20}{9} \cdot \frac{31}{5} = \frac{14}{3} + \frac{4}{9} \cdot 31 = \frac{14}{3} + \frac{124}{9} = \frac{42 + 124}{9} = \frac{166}{9} = 18\frac{4}{9}$
д) $(\frac{4}{7} - \frac{3}{5}) \cdot 35 = (\frac{20 - 21}{35}) \cdot 35 = (-\frac{1}{35}) \cdot 35 = -1$
е) $(-1\frac{1}{3} - 1\frac{1}{9}) \cdot 18 = (-\frac{4}{3} - \frac{10}{9}) \cdot 18 = (-\frac{12 + 10}{9}) \cdot 18 = -\frac{22}{9} \cdot 18 = -22 \cdot 2 = -44$
**Ответ:**
a) -0.08
б) 3/13
в) -25/66
г) 18 4/9
д) -1
е) -44